The political heritage of Islam - Ismael, Tareq Y. 1939-; Ismael, Jacqueline S. (1991)
"Islam is not just a religious order. It is a complete way of life for the individual, the society, the state, and the nation." The authors give information on the Qur'an and the Shari'ah, the Ummah, essential religious beliefs of Islam, religious duties of the faithful Muslim, the Islamic value system, Islamic law, the Islamic state, secularism, and Islam today. (DÜI-Mjr)
Keywords: Koran; Islam; Staat; Laizismus; Islamisches Recht; Religion; Geschichte; Islamische Länder/Islamische Welt -- Islam -- Koran -- Staat -- Laizismus -- Islamisches Recht -- Religionsgeschichte; Islamische Staaten